The shift : surviving and thriving after moving from conservative to progressive Christianity - Martin, Colby (Fortress Press, 2020)
When Christians are kicked out of their conservative churches or leave because they no longer feel at home, they undertake a serious shift. Colby Martin has traversed this treacherous territory, survived its hardships, and is now sharing what he's learned. This friendly survival guide will prepare readers for the pitfalls awaiting them as they shift out of their conservative world, and it will equip them for a more abundant, thriving, and peace-filled spiritual life.